The Analysis of Pancreatic Duodenal Homeobox 1 (PDX-1) Gene Mutation Based on Blood Glucose Level on Domestic Cats (Felis catus) Post Ovaryohisterectomy - Putri, Hana Mitsuki; Aulani'am, Aulani'am; Nurmaningdyah, Ajeng Aeka; Prasetyo, Dodik; Permata, Fajar Shodiq (Veterinary Biomedical and Clinical Journal, 2021)
Ovariohysterectomy (OH) in domestic cats causes several side effects, including obesity. Obesity is closely related to diabetes. The glucoregulatory gene that will cause insulin resistance if there is a gene mutation is the PDX-1 gene. This insulin resistance will have a very immediate effect on blood glucose in the body. The study examined the relationship between PDX-1 gene polymorphisms and blood glucose levels in domestic cats with OH. The method used in this study was in vitro PCR amplification of the PDX-1 gene with Forward primers 'CCG AGC TGT CAA AGC TAG CG' and Reverse 'GAA CCG GTA GAG GGT CTT GG' and followed by sequencing of PCR products. The results showed fundamental differences in the base sequence in the PDX-1 gene sequences at c.435G>A, c.927A>T, and c.584A>G. The fundamental difference in the PDX1 gene sequence is a silent mutation